Technical note: 9-month repositioning accuracy for functional response assessment in head and neck chemoradiotherapy. - Partridge, M; Powell, C; Koopman, M; Humbert Vidan, L; Newbold, K (2012)
The use of thermoplastic immobilisation masks in head and neck radiotherapy is now common practice. The accuracy of these systems has been widely studied, but always within the context and time frame of the radiation delivery-some 6-8 weeks. There is growing current interest in the use of functional imaging to assess the response to treatment, particularly in the head and neck. It is therefore of interest to determine the accuracy with which functional images can be registered to baseline CT over the extended periods of time used for functional response assessment: 3-6 months after radiotherapy. In this study, repeated contrast-enhanced diagnostic quality CT and mid-quality localisation CT from a positron emission tomography/CT scanner were available for five time points over a period of 9 months (before, during and up to 6 months after chemoradiotherapy) for a series of eight patients enrolled in a clinical pilot study. All images were acquired using thermoplastic immobilisation masks. The overall set-up accuracy obtained from this 9-month study of 5.5 ± 3.2 mm (1 standard deviation) and 1.9 ± 1.3° (1 standard deviation) is in agreement with published data acquired over 6-8 weeks. No statistically significant change in set-up error was seen with time. This work indicates that thermoplastic immobilisation masks can be used to accurately align multimodality functional image data for assessment of the response to treatment in head and neck patients over extended follow-up periods.